Following the Equator: A Journey Around the World. Part 7 - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Following the Equator: A Journey Around the World. Part 7" by Mark Twain is a travelogue published in 1897. Facing bankruptcy from a failed business investment, the sixty-year-old Twain embarked on a lecture tour through the British Empire. This work chronicles his journey with perceptive observations on people, cultures, religion, politics, and customs encountered along the way. Through satirical social commentary and even embedded fictional tales, Twain transforms his financial necessity into sharp-eyed reflections on the world's diverse societies and their peculiarities. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Following_the_Equator
Release date is 2004-06-24
Produced by David Widger
Keywords: Voyages around the world; Twain, Mark, 1835-1910 -- Travel; Equator -- Description and travel